The Role of Employee Adaptive Competence and Operational Resilience in a Risk Management Perspective to Maintain Service Continuity at PT Bank Sumut Syariah Pematangsiantar - Nadhilah Nazlah Nasution; Sri Ramadhani; Imsar (Danadyaksa: Post Modern Economy Journal, 2026)
This research aims to analyze the role of employee adaptive competence in supporting operational risk management, examine the development of operational resilience, and identify obstacles in maintaining service continuity at PT Bank Sumut Syariah Pematangsiantar Branch. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observations, and documentation. The results show that employee adaptive competence plays a crucial role in mitigating risks, but the level of readiness is not uniform among individuals, leading to inconsistent responses to disruptions. Operational resilience at the branch level has been established through experience and coordination, yet it remains situational and not yet systematically structured. Furthermore, operational risk management was found to be responsive in handling technical and non-technical disruptions. The study concludes that service continuity still relies heavily on individual initiatives rather than organizational systems. It is recommended that the organization strengthen adaptive competence uniformly and integrate a more proactive Enterprise Risk Management (ERM) framework.